2007
DOI: 10.1099/mic.0.2007/009316-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter sakazakii invades brain capillary endothelial cells, persists in human macrophages influencing cytokine secretion and induces severe brain pathology in the neonatal rat

Abstract: Enterobacter sakazakii is an opportunistic pathogen associated with contaminated powdered infant formula and a rare cause of Gram-negative sepsis that can develop into meningitis and brain abscess formation in neonates. Bacterial pathogenesis remains to be fully elucidated. In this study, the host inflammatory response was evaluated following intracranial inoculation of Ent. sakazakii into infant rats. Infiltrating macrophages and neutrophils composed multiple inflammatory foci and contained phagocytosed bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 32 publications
(15 reference statements)
3
106
2
3
Order By: Relevance
“…Cronobacter appear to evade the host's immune system by adapting to a lifestyle of replication in the intracellular environment confined within macrophages. Townsend et al (2007b) showed that that Cronobacter can persist within human U937 macrophages and survival varied between strains, Cronobacter persisting intracellularly for up to 96 h. In another study, most Cronobacter strains persisted in macrophages for 48 h (Townsend et al, 2008). These results suggest that Cronobacter possess virulence properties that enable them to tolerate the intracellular environment of macrophages.…”
Section: Evading the Immune Responsementioning
confidence: 58%
See 3 more Smart Citations
“…Cronobacter appear to evade the host's immune system by adapting to a lifestyle of replication in the intracellular environment confined within macrophages. Townsend et al (2007b) showed that that Cronobacter can persist within human U937 macrophages and survival varied between strains, Cronobacter persisting intracellularly for up to 96 h. In another study, most Cronobacter strains persisted in macrophages for 48 h (Townsend et al, 2008). These results suggest that Cronobacter possess virulence properties that enable them to tolerate the intracellular environment of macrophages.…”
Section: Evading the Immune Responsementioning
confidence: 58%
“…Kothary et al (2007) identified the gene locus of zinc-containing metalloprotease (zpx) -a protein that caused rounding of CHO cells in tissue culture. In addition, the presence of putative sodA genes might provide resistance for Cronobacter against intracellular macrophage oxidase and acidic conditions, and may contribute to its intracellular persistence (Townsend et al, 2007b). However, these genes and OmpA and OmpX were found in all Cronobacter spp., and thus cannot be responsible for the variation in pathogenicity among the different Cronobacter strains (Joseph et al, 2012c).…”
Section: Virulence Genes and Plasmidsmentioning
confidence: 91%
See 2 more Smart Citations
“…The pathogen is reported to persist within human macrophages indicating that the Cronobacter possessed virulence properties that make it allows to tolerate the intracellular environment of macrophages. 124,125 Conclusions and future perspectives Cronobacter spp is a newly classified genus and more research is yet to be completed for better understanding this unique group of organism. As a virulent species, it causes high mortalities in the neonates, therefore, it is important to understand which gene products are responsible for the pathogenicity of the bacteria and how the expression of these virulence factors is regulated.…”
Section: Biofilm Formationmentioning
confidence: 99%